ANALISIS HAMBATAN TERHADAP VARIASI SUDUT STERN WEDGE PADA LAMBUNG KAPAL DENGAN METODE CFD - Naufal Azzam Dzaky (2023)
The stern part of a ship generally encounters an inefficient flow pattern when sailing. Efforts to reduce drag on a ship are carried out with the right design in hydrodynamics and propulsion. This study aims to compare the use of stern wedge on the hull of the ship against the resistance of the ship. For hydrodynamic investigations and model calculations using Computional Fluid Dynamic (CFD) with ANSYS software. The hydrodynamic analysis of the hull is carried out on the components of total resistance, friction resistance, friction resistance, and wave resistance with a variety of angles for the stern wedge (1°, 3°, 5°, 7°, 9°). Simulation of drag is carried out on each variation of one to six at speeds of 2, 5 and 8 m/s, among the angle variations, namely angles of 1°, 3°, 5°, 7° and 9°, the results of the total drag analysis that has the minimum drag is in model 1, namely with a wedge length of 0.2 (B) angle of 1 degree where the total drag is 9.0 N. The results of the simulation of resistance to variations in ship trim angles, namely trim angles of 1 °, 3 °, and 5 ° with a constant speed of 5 m / s get the angle that has the smallest resistance is the angle of 1 °, for the model that has the smallest resistance at an angle of 1° is model 1, while for angles of 3° and 5 °, the model that has the smallest resistance is model 4.